2013
DOI: 10.6026/97320630009054
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral potential of 4-hydroxypanduratin A, secondary metabolite of Fingerroot, Boesenbergia pandurata (Schult.), towards Japanese Encephalitis virus NS2B/NS3 prote

Abstract: 4-hydroxypanduratin A is a secondary metabolite of Boesenbergia pandurata Schult. (Fingerroot) plant with various pharmacological activities such as neuroprotective, potent antioxidant, antibacterial and antifungal. Flaviviral NS2B/NS3 protease activity is essential for polyprotein processing and viral replication for Japanese Encephalitis Virus (JEV), a major cause of Acute Encephaltis in Asia. Inhibition of formation of this complex by arresting the binding of NS2B with NS3 would reduce the enzyme's activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Flavonoids namely (Kaempferol, Daidzein) and plant secondary metabolite like 4-hydroxyl panduratin A has proved to be effective inhibitors against JEV. 11,12 Literature review has shown that Flavonoids and Isoflavones (class of phytoestrogens) inhibit virus infectivity. Flavonoids affect virus binding to cell membranes, entry into the cell, replication, viral protein translation within the host cell and formation of certain glycoprotein complexes of the virus envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids namely (Kaempferol, Daidzein) and plant secondary metabolite like 4-hydroxyl panduratin A has proved to be effective inhibitors against JEV. 11,12 Literature review has shown that Flavonoids and Isoflavones (class of phytoestrogens) inhibit virus infectivity. Flavonoids affect virus binding to cell membranes, entry into the cell, replication, viral protein translation within the host cell and formation of certain glycoprotein complexes of the virus envelope.…”
Section: Introductionmentioning
confidence: 99%
“…14 In silico screening of 4-hydroxypanduratin A showed anti-viral activity against JEV NS2B/NS3 protease. 12 Besides these compounds, antibiotic group compounds (Tetracycline and Aminoglycosides) have shown promising effects against flaviviral diseases. Broad-spectrum antibiotics like Minocycline tetracycline inhibited JEV and West Nile virus (WNV) induced infection in experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…This binding mode proved the hypothesis that the andrographolide derivatives bind to ACZ97474 with almost hydrophobic interactions and it should be the pre-organized shape binding between the rigid structure of andrographolide analogues and the binding pocket of ACZ97474. All the docking and interaction analysis were carried out as per our previous studies [32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…[94,95] Minocycline Antioxidant [99,100] Arctigenin Antioxidant [101] Fenofibrate Antioxidant [102] Curcumin Antioxidant [103] Pentoxifylline Assembly or Release [105] Nitazoxanide Early/mid-replication cycle [107] Nucleic acid-based siRNA C, M, E, NS1, NS3, NS4B, NS5 [109][110][111][112][113][114][115] PNA UTR [119] Morpholino oligomer UTR [121,122] Virus replication cycle-based Heparan sulfate Receptor binding [123][124][125] E-binding peptide Receptor binding [126] NSQ Attachment [127] Indirubin Attachment [128] Bovine lactoferrin Receptor binding [129] Griffithsin Receptor binding [130] Recombinant E Receptor binding [131,132] MCPIP1 RNA replication [133] Kaempferol RNA replication [134] SCH16 Translation [138,139] In silico modeling-based Ivermectin NS3 [146] 4-hydroxypanduratin NS2B/NS3 [147] C randomized, double-blind, human clinical trial conducted in India [95]. A variety of virus-infected cells have been shown to produce reactive oxygen species (ROS), which are associated with viral pathogenicity, for example, by inducing cellular apoptosis [96].…”
Section: Categorymentioning
confidence: 99%
“…Ivermectin, which is used as an anthelmintic drug, displayed anti-JE activities in vitro [146]. 4-Hydroxypanduratin A, a secondary metabolite of Boesenbergia pandurata Schult, was selected in silico to interrupt the interaction between the NS2B and NS3 proteins by binding to NS2B, although no in vitro and in vivo evaluations have been performed [147].…”
Section: In Silico Modeling-based Antiviral Drugsmentioning
confidence: 99%